Determinants of corporate cash holdings in the Nigerian capital market - Ishola, Abdurraheem Ibraheem (2020)
This research investigates factors that determine corporate cash holdings of listed companies on the Nigerian Stock Exchange (NSE) over the period of 2005-2019. Although, a number of factors have been examined by prior studies, however, factors affecting companies that are financially constrained differ from non-financially constrained companies have received limited attention. Factors that are examined in this study are financial constraints, cash flow, leverage, company size, age and performance, networking capital, asset utilization, tangibility, growth opportunities and dividend payout. This study uses a static and dynamic panel regression technique to identify the determinants of corporate cash holdings in Nigeria. Results of this study reveal that financial constraints, asset utilization, cash flow to asset ratio, networking capital, tangibility and growth opportunities are significant determinants of corporate cash holdings of companies listed on the NSE. It further shows that cash flow has a negative relationship with corporate cash holdings which is supported by the trade-off theory. Further, company size has a positive relationship with corporate cash holdings which is supported by the pecking order theory. Meanwhile, growth opportunity has a negative relationship with corporate cash holdings and is in line with the free cash flow theory. The major contribution of the research is that it adds and improves the current literature on the factors that determine the corporate cash holdings for an emerging market like Nigeria.